Новый вид щетинкочелюстных Sagitta dimitryi sp. nov. (Chaetognatha, Sagittoidea) из Охотского моря (Северо-Западный Сахалин) - Касаткина, А. П.; Васильева, Л. Е. (My University, 2024)
В статье описан новый вид щетинкочелюстных Sagitta dimitryi sp. nov., обнаруженный в водах Охотского моря у северо-западной части Сахалина. Дана таблица определительных ключей для видов рода Sagitta с включением Sagitta dimitryi sp. nov. Обсуждается родство современных Sagitta с древними Chaetognatha, в том числе возможные причины эволюции кишечного аппарата.
A new species of arrow worms, Sagitta dimitryi sp. nov. (Chaetognatha, Sagittoidea), from the Sea of Okhotsk (Northwest Sakhalin)
A new species of chaetognaths, Sagitta dimitryi sp. nov., was discovered in the waters of the Sea of Okhotsk, near the northwestern part of Sakhalin. The aim of this article is to describe the new species. A table of identification keys for species of the genus Sagitta is given, including Sagitta dimitryi sp. nov. The relationship of modern Sagitta with ancient Chaetognatha is discussed, including possible reasons for the evolution of the intestinal apparatus.
Keywords: Sagitta dimitryi sp. nov., Chaetognatha, Сахалин, Охотское море; Sagitta dimitryi sp. nov., Chaetognatha, Sakhalin, Sea of Okhotsk